Sri Lankan Travel & Tourism Industry: Recent Trends and Future Outlook towards Real Estate Development - Munasinghe, L.M.; Gunawardhana, T.; Ariyawansa, R.G. (My University, 2018)
Tourism is considered as an important economic activity around the world due to its direct economic impact as well as it's significant indirect and induced impacts. According to the World Travel and Tourism Council, Travel & Tourism industry is one of the world’s largest economic sectors accounts for 10.4% of global GDP and 313 million jobs, or 9.9% of total employment, in 2017. Direct and indirect impact of this on real estate development in the world is tremendous in terms of accommodation, catering to food and beverages, leisure pleasure & relaxation and so on. In Sri Lanka, tourism is the third largest export earner in the economy and during the past five years, there has been an unprecedented growth in the industry. But tourism in Sri Lanka has much more untapped potential where the industry is poised to offer great growth and investment potential. And through right policies and investment decisions, Sri Lanka can leverage the economic prospects of Travel & Tourism Industry. This study analyses the importance of travel & tourism industry in terms of real estate development and reviews major trends that are shaping the growth and development of the travel & tourism industry in Sri Lanka. This will be important to policymakers in preparing right policies and in making the right investment decisions. The analysis is based on modified Tourism Satellite Account: Recommended Methodological Framework 2008 (TSA: RMF 2008) published by World Travel & Tourism Council, and carried out analyzing both academic and nonacademic publications, including published journal articles, annual and quarterly reports published by United Nations’ World Tourism Organization, World Travel & Tourism Council, World Economic Forum and Sri Lanka Tourism Development Authority and through the raw data obtained by World Travel & Tourism Council for Sri Lanka. As per the analysis, the future outlook is bright for the tourism sector in Sri Lanka, and the country is expected to maintain a high rate of growth well into the next decade.
Keywords: tourism trends, real estate trends, real estate development, travel & tourism industry, Sri Lanka